Impact assessment of coal mining induced subsidence on native soil of South Eastern Coal Fields: India - Vishwakarma A.K.; Behera T.; Rai R.; Sonkar A.K.; Singh A.P.; Shrivastva B.K. (My University, 2025)
Understanding the consequences of mining is most important in order to prevent negative outcomes for the environment as natural systems are used by humans for agriculture/silviculture. The present manuscript deals with the impact of subsidence due to underground coal mining on native soil. Depth-wise changes in soil texture and nutrient components in four layers; 0–15 cm, 16–30 cm, 31–45 cm and 46–60 cm were quantified along the subsidence prone land of the study area in top (within the extension zone; Zone I), middle (within inner-edge zone; Zone II) and bottom (around centre of the subsidence trough; Zone III) of a three and half year mining subsided land and compared it with soil texture and nutrient component status of an adjacent undamaged zone (UZ). An alteration in the Physicochemical characteristics of the soil after subsidence was observed. It had a positive impact on most of the soil characteristic parameters at Zone III. Available nitrogen, phosphorous and potassium (AN, AP and AK) were increased by 13.00%, 44.47% and 26.7%, respectively in 0–15 cm layer; 16.42%, 45.12% and 28.08%, respectively in 16–30 cm layer; 15.74%, 47.45% and 22.97%, respectively in 31–45 cm layer and 14.86%, 38.94% and 18.53%, respectively in 46–60 cm layer. A significant increase in silt + clay content, organic carbon and electrical conductivity were also reported. © 2020, Springer Nature Switzerland AG.